2003
DOI: 10.1021/jp022692e
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Isolation and Theoretical Study of the Photochemical Reaction of PH3 with OVCl3 and CrCl2O2

Abstract: The matrix isolation technique has been combined with theoretical calculations to identify and characterize the photoproducts in the reaction of PH 3 with OVCl 3 and CrCl 2 O 2 . In contrast to previous studies, HCl elimination from an initial complex is not observed. Instead, a number of product bands, some quite intense, were observed and have been assigned to phosphine oxide, H 3 PO, through the direct O atom transfer from the transition metal oxo compound. This identification was supported by extensive iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…However, subsequent irradiation of these matrices led to the formation of product bands in a manner that is similar to the previous systems studied in this lab [23,[32][33][34]. Since diffusion of most molecules does not occur within the argon lattice at 14 K, for a photochemical reaction to occur after twin jet deposition the reactants must be trapped within the same matrix cage.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…However, subsequent irradiation of these matrices led to the formation of product bands in a manner that is similar to the previous systems studied in this lab [23,[32][33][34]. Since diffusion of most molecules does not occur within the argon lattice at 14 K, for a photochemical reaction to occur after twin jet deposition the reactants must be trapped within the same matrix cage.…”
Section: Discussionmentioning
confidence: 53%
“…Past studies in this laboratory have examined the matrixisolated products of the thermal and photochemical reactions of CrCl 2 O 2 , OVCl 3 , and OVF 3 with organic and inorganic substrates [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Specifically, two recent studies in this lab [33,34] examined the reactions of CrCl 2 O 2 with benzene and with methyl-substituted benzenes.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Finally, Ault and Kayser observed the formation of H 3 PO in argon matrices after photochemical irradiation of a mixture of VOCl 3 , CrO 2 Cl 2 , and PH 3 . [5] Both molecules have been studied by theoretical methods. [6] Application of an adequate phosphorus basis set has recently shown that, in contrast with previous ab initio studies, [7] I is more stable than II by only about 1 kcal mol À1 in the gas phase.…”
mentioning
confidence: 99%
“…Phosphine (PH 3 ) reacts with OVCl 3 and CrO 2 Cl 2 on irradiation in a low temperature matrix to give the phosphine oxide OPH 3 by O-atom transfer. 281 There was no sign of HCl elimination here. With water both OVCl 3 and CrO 2 Cl 2 react to give 1:1 complexes which do undergo HCl elimination on photolysis and l 4 300 nm.…”
Section: Groups 4 Tomentioning
confidence: 79%